Utilizing a Segmented Fuel Cell to Study the Effects of Electrode Coating Irregularities on PEM Fuel Cell Initial Performance. Issue 3 (27th April 2017) - Phillips, A.; Ulsh, M.; Porter, J.; Bender, G.
Abstract: An understanding of the impact of coating irregularities on beginning of life polymer electrolyte fuel cell (PEMFC) performance is essential to develop and establish manufacturing tolerances for its components. Coating irregularities occurring in the fuel cell electrode can either possess acceptable process variations or potentially harmful defects. A segmented fuel cell (SFC) is employed to understand how 100% catalyst reduction irregularities ranging from 0.125 to 1 cm 2 in the cathode electrode of a 50 cm 2 sized cell impact spatial and total cell performance at dry and wet humidification conditions. By analyzing the data in a differential format the local performance effects of irregularity sizes down to 0.25 cm 2 were detected in the current distribution of the cell. Slight total cell performance impacts, due to irregularity sizes of 0.5 and 1 cm 2, were observed under dry operation and high current densities.